Adjuvant S‐1 vs gemcitabine for node‐positive perihilar cholangiocarcinoma: A propensity score‐adjusted analysis. (22nd June 2021) - Takahashi, Daigoro; Mizuno, Takashi; Yokoyama, Yukihiro; Igami, Tsuyoshi; Yamaguchi, Junpei; Onoe, Shunsuke; Watanabe, Nobuyuki; Maeda, Osamu; Ando, Masahiko; Ebata, Tomoki
Abstract: Background: The efficacy of adjuvant chemotherapy for biliary cancers remains controversial because of conflicting results from previous phase 3 studies that used different key drugs and enrolled patients with heterogeneous tumor sites and disease stages. Fluoropyrimidine seems more beneficial than gemcitabine (GEM) combination regimens in the adjuvant setting; however, data comparing the survival benefit between GEM‐ and fluoropyrimidine‐based regimens are lacking. Methods: Patients who underwent resection for node‐positive perihilar cholangiocarcinoma were included. The patients who underwent adjuvant chemotherapy were divided into the S‐1 and GEM groups according to the regimen. The recurrence‐free survival (RFS) and the overall survival (OS) were compared between the groups and adjusted with propensity scores generated from 14 potentially confounding clinicopathological factors. Results: In total, 186 patients (Surgery alone, n = 71; S‐1, n = 60; GEM, n = 55) were included. The S‐1 and GEM completion rates were 75% and 65%, respectively. Among the patients who underwent adjuvant therapy, the RFS was longer in the S‐1 group patients than the GEM group patients (median, 24.4 months vs 14.9 months; P = .044) whereas the OS was not significantly different between the groups (median, 48.5 months vs 35.0 months; P = .324). After propensity score adjustment, the differences in RFS and OS between the groups were more evident (HR: 2.696, 95% CI: 1.739‐4.180 P < .001; HR: 1.988, 95% CI: 1.221‐3.238, P < .001, respectively). Conclusions: Compared with adjuvant GEM monotherapy, adjuvant S‐1 monotherapy may improve survival in node‐positive perihilar cholangiocarcinoma patients. Abstract : Highlight Takahashi and colleagues evaluated the survival benefit of adjuvant S‐1 monotherapy over gemcitabine monotherapy for biliary tract cancer in patients after hepatectomy for node‐positive perihilar cholangiocarcinoma, a group with relatively homogenous tumor subtype and stage. S‐1 monotherapy was associated with longer recurrence‐free and overall survival on multivariable and propensity‐score adjusted analysis.